1998
DOI: 10.1007/s001250050911
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of cell adhesion molecules in the pathogenesis of diabetic neuropathy

Abstract: Peripheral neuropathy is one of the commonest complications of diabetes mellitus with a prevalence of around 30±45 % [1±3]. The majority of patients will have developed neuropathy 10±20 years after the onset of diabetes [4] and it is an important cause of foot ulceration, Charcot joints and amputation, with increasing morbidity and mortality. There is therefore an urgent need for prevention of diabetic neuropathy and its sequelae.The exact pathogenesis of diabetic neuropathy is unclear, with both metabolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…Soluble forms of CAMs are also considered to be an index of endothelial activation or even a molecular marker of early atherosclerosis [26]. In one study, plasma CAMs were associated with the risk of deterioration of peripheral neuropathy in diabetic patients [27]. Our findings suggest that diabetic patients with ED present an impairment of endothelial functions and indices of endothelial activation more marked than diabetic patients without ED.…”
Section: Discussionmentioning
confidence: 59%
“…Soluble forms of CAMs are also considered to be an index of endothelial activation or even a molecular marker of early atherosclerosis [26]. In one study, plasma CAMs were associated with the risk of deterioration of peripheral neuropathy in diabetic patients [27]. Our findings suggest that diabetic patients with ED present an impairment of endothelial functions and indices of endothelial activation more marked than diabetic patients without ED.…”
Section: Discussionmentioning
confidence: 59%
“…Increasing plasma levels of soluble cell adhesion molecules (sICAM-1, E-selectin) were associated with decreasing peroneal nerve conduction velocity during a 5-year period in a small group of diabetic patients, which indeed indicated a vascular involvement in the development and progression of DSPN (28). Elevated concentrations of cell adhesion molecules such as sICAM-1 in the circulation result from increased expression and/or shedding of these proteins from the cell surface in response to endothelial activation.…”
Section: Discussionmentioning
confidence: 87%
“…An increase in the level of CAMs has been demonstrated in diabetic patients with microvascular disease. [13][14][15] In particular, a previous study on peroneal nerve function showed significant association between increasing levels of VCAM and worsening peroneal nerve function. [15] In our study, despite the lack of signiÞ cant changes in the serum VCAM-1 levels with glycemic improvement in either group, patients with neuropathy had significantly higher VCAM-1 values at baseline compared to those without.…”
Section: Journal Of Medical Sciencesmentioning
confidence: 94%
“…[13][14][15] In particular, a previous study on peroneal nerve function showed significant association between increasing levels of VCAM and worsening peroneal nerve function. [15] In our study, despite the lack of signiÞ cant changes in the serum VCAM-1 levels with glycemic improvement in either group, patients with neuropathy had significantly higher VCAM-1 values at baseline compared to those without. [8][9][10][11][12][13][14][15] We also found that an increase in VCAM-1 levels correlated with an increase in AGE, supporting Þ ndings from other studies which showed that AGE products result in the release of CAMs through interaction with the receptors for AGE (RAGE).…”
Section: Journal Of Medical Sciencesmentioning
confidence: 94%
See 1 more Smart Citation